COLUMNEA FIGUEROAE, A NEW SPECIES OF GESNERIACEAE FROM LAS ORQUÍDEAS NATIONAL NATURAL PARK (ANTIOQUIA, COLOMBIA) (2014)
A new species of Columnea (Gesneriaceae) recently found in a premontane forest in the National Natural Park Las Orquídeas (“Cordillera Occidental”), in the Department of Antioquia in Colombia, is described and illustrated.